A comparative analysis of non-communicable disease risk among adolescents aged 12 to 18 in the Eastern Cape, South Africa, with regard to sex, school quintiles, and perceived stress - Mathe, Avela; van Gent, Maria Maya; van Niekerk, Rudolph Leon (Frontiers in Public Health, 2025)
BackgroundNon-communicable diseases (NCDs) are a growing concern in low- and middle-income countries, especially among adolescents. Recent data indicate a rise in NCD cases within this group. Despite the increasing prevalence of NCD risk factors, limited research has explored the relationship between perceived stress and NCDs.Study aimTo compare adolescents aged 12 to 18 years who are at risk for NCDs with those who are not at risk, considering sex, school quintiles, and perceived stress.SettingsThe study involved 266 adolescents selected through stratified random sampling from seven schools in two Eastern Cape districts.MethodsIt assessed anthropometric and physiological measurements and perceived stress levels. Descriptive statistics were used to summarize data, while independent samples t-tests analyses were employed to compare groups. Logistic regression was utilized to predict probability.ResultsMost physical and physiological assessments were normal, except for females’ elevated BMI (24.52 ± 6.11), classifying them as overweight. Perceived stress did not differ significantly between at-risk and not-at-risk adolescents, although at-risk females reported higher stress levels than males. Perceived stress was consistently higher among adolescents from Quintiles 4–5 schools across both at-risk and not-at-risk groups. Logistic regression analysis indicated that sex was the significant predictor of NCD risk, with females being four times more likely to develop NCD risk factors than males, whereas school quintile was not a significant predictor.ConclusionThe study highlights a greater risk of NCD development among female adolescents, who also experience elevated levels of perceived stress. Recommendations to address these findings include specific strategies that reduce this population’s risk factors.